Claudin7-dependent exosome-promoted reprogramming of nonmetastasizing tumor cells - Kyuno, Daisuke; Zhao, Kun; Schnölzer, Martina; Hackert, Thilo; Zöller, Margot (International journal of cancer, 2019)
Claudin7 (cld7) is a cancer-initiating cell (CIC) marker in gastrointestinal tumors, a cld7-knockdown (kd) being accompanied by loss of tumor progression. Tumor exosomes (TEX) restoring CIC activities, we explored the contribution of cld7. This became particularly interesting, as tight junction (TJ)- and glycolipid-enriched membrane domain (GEM)-derived cld7 is recruited into distinct TEX. TEXs were derived from CIC or cld7kd cells of a rat pancreatic and a human colon cancer line. TEX derived from pancreatic cancer cld7kd cells rescued with palmitoylation site-deficient cld7 (cld7mP) allowed selectively evaluating the contribution of GEM-derived TEX, only palmitoylated cld7 being integrated into GEM. Cld7 CIC-TEX promoted tumor cell dissemination and metastatic growth without a major impact on proliferation, apoptosis resistance and epithelial-mesenchymal transition. Instead, migration, invasion and (lymph)angiogenesis were strongly supported, only migration being selectively fostered by GEM-derived cld7 TEX. CIC-TEX coculture of cld7kd cells uncovered significant changes in the cld7kd cell protein and miRNA profiles. However, changes did not correspond to the CIC-TEX profile, CIC-TEX rather initiating integrin, protease and RTK, particularly lymphangiogenic receptor activation. CIC-TEX preferentially rescuing cld7kd-associated defects in signal transduction was backed up by an RTK inhibitor neutralizing the impact of CIC-TEX on tumor progression. In conclusion, cld7 contributes to selective steps of the metastatic cascade. Defects of cld7kd and cld7mP cells in migration, invasion and (lymph)angiogenesis are effaced by CIC-TEX that act by signaling cascade activation. Accordingly, RTK inhibitors are an efficient therapeutic defeating CIC-TEX.
Gesehen am 21.10.2019